Awareness and Attitude Towards Exclusive Breastfeeding Among Mothers of Urban and Rural Community of Jhapa District - Neupane, Pushpa (Medical Journal of Eastern Nepal, 2025)
Background: Breastfeeding is the way of providing nutrients to young infants for proper growth and development whereas Exclusive Breastfeeding means a baby receives only breast milk without additional food or drink, including water until six months of age. Breastfeeding is the survival intervention for infant which is effective in reducing infant morbidity and mortality. Methods: Descriptive comparative research design was used for the study to compare awareness and attitude towards Exclusive Breastfeeding among mothers residing in selected rural and urban community. Non probability sampling techniques was used with sample size 192. Results: Among 192 mothers, more than half (53.2% and 53.0%) of mothers had good level of awareness in rural and urban community respectively. Among 192 mothers majority of mothers (85.4% and 82.3%) respectively in rural and urban community had positive attitude towards exclusive breastfeeding. The data shows that there is no significant difference in the level of awareness and attitude regarding exclusive breastfeeding among mothers residing in rural and urban community. Conclusion: Among 192 mothers, more than half of the mothers had good level of awareness regarding exclusive breastfeeding where as two thirds of the mothers had positive attitude towards exclusive breastfeeding in both rural and urban community.